Structural and performance of chitosan-based polymer composites for electrical applications - Norfatihah, Mazuki; Mohd Saiful Asmal, Rani; Nuraziliana, Muhd Ghazali; Nurhasniza, Mamajan Khan; Muhammad Nor Arifin, Yaakob; Ahmad Salihin, Samsudin (Woodhead Publishing, 2024)
Natural polymer, chitosan has been the subject of widespread investigations over the past decade due to its desired features, including nontoxicity, biodegradability, and good compatibility. Polymer composite electrolytes-based natural polymer has indicated good properties as a biocompatible material for various applications. It contains amino and hydroxyl active groups, which make it an excellent material for modifying electrolytes for electrochemical devices. However, chitosan has limited electrical conductivity, which has been considered a concern among researchers. To overcome this limitation, several approaches have been employed. Among approaches are by combining chitosan with conducting polymer, adding ionic dopant salt, and plasticizer/fillers. Therefore the main objective of this chapter is to provide an up-to-date review of the recent studies conducted in the development of polymer composite electrolytes-based chitosan, which focuses on the overview of chitosan as host polymer, methods of their preparation, and the ways to alter their characteristics. Moreover, the recent progress usage of chitosan composite as an electrolyte and its performance in electrical energy devices are also discussed.